Future profitability and stock returns of innovative firms: a pitch. Issue 1 (22nd January 2021) - Bedford, Anna; Vojvoda, Kristina; Ma, Le; Ma, Nelson
Abstract : Purpose: This research letter outlines the "AFAANZ shark pitch 2020" research journey and reflects on the application of the pitch template to the authors' research topic on innovation, future profitability and stock returns. Design/methodology/approach: This study begins by outlining how the research started, followed by the choice of authors' replication study. This study then outlines the authors' interactions with the corresponding author of the original study and the journal editor. The authors also detail their personal journey of using the pitch template. Findings: The pitch template facilitated the identification of a replication study that has significant impact in informing Australian policy decisions. It allowed the authors to succinctly articulate and refine their research ideas. Originality/value: This research letter highlights authors' mistakes in using the pitch template and what they learned from interacting with the original authors and journal editor.